2013
DOI: 10.3892/or.2013.2628
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induced by PGC-1β in breast cancer cells is mediated by the mTOR pathway

Abstract: The peroxisome proliferator-activated receptor-γ (PPAR-γ) coactivator-1β (PGC-1β) is a well-established regulator of mitochondrial biogenesis. However, the underlying mechanism of PGC-1β action remains elusive. This study reveals that knockdown of endogenous PGC-1β by short-hairpin RNA (shRNA) leads to a decrease in the expression of mammalian target of rapamycin (mTOR) pathway-related genes in MDA-MB-231 cells. After knockdown of PGC-1β, phosphorylation of AMP-activated protein kinase (AMPK), phosphorylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…However, a recent study suggested that long-term PGC1β overexpression could lead to apoptosis, autophagy, and atrophy in the skeletal muscle of mice (43). Additionally, it has been suggested that PGC1β overexpression decreases apoptosis in breast cancer cells (44). In our study, we noticed a dynamic change of either miR-378 or PGC1β mRNA expression on metabolic stress ( Fig.…”
Section: Discussionmentioning
confidence: 43%
“…However, a recent study suggested that long-term PGC1β overexpression could lead to apoptosis, autophagy, and atrophy in the skeletal muscle of mice (43). Additionally, it has been suggested that PGC1β overexpression decreases apoptosis in breast cancer cells (44). In our study, we noticed a dynamic change of either miR-378 or PGC1β mRNA expression on metabolic stress ( Fig.…”
Section: Discussionmentioning
confidence: 43%
“…Furthermore, suppressing PGC1␤ and ERR␣ expression decreased colon tumor cell viability and anchorage-independent growth and delayed tumor formation in nude mice, making them potential targets in cancer therapy. PGC1␤ and ERR␣ have been studied extensively as metabolic regulators that promote tumorigenesis in breast cancer (45)(46)(47)(48)(49). Breast cancer has a low incidence of activating Ras mutations but are often driven by the overexpression of ERBB2, which signals through Ras (50).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the levels of PGC-1β and mTOR correlated with overall mitochondrial activity in breast cancer samples. Moreover, the knockdown of endogenous PGC-1β, leads to a decreased expression of mTOR pathway related genes and induces apoptosis in MDA-MB-231 cells (143). Interestingly, it was demonstrated that the branched chain amino acid transaminase 1 (BCAT1) actives mTORC1 and in consequence promotes the mitochondrial biogenesis, ATP production and defense of oxidative stress (143).…”
Section: Mitochondrial Biogenesis and Mitophagy: Mtorc1 In Cancermentioning
confidence: 99%
“…Moreover, the knockdown of endogenous PGC-1β, leads to a decreased expression of mTOR pathway related genes and induces apoptosis in MDA-MB-231 cells (143). Interestingly, it was demonstrated that the branched chain amino acid transaminase 1 (BCAT1) actives mTORC1 and in consequence promotes the mitochondrial biogenesis, ATP production and defense of oxidative stress (143). The inhibition of mTORC1 with rapamycin, neutralized the roles of BCAT1 in mitochondrial function and breast cancer cell growth (143).…”
Section: Mitochondrial Biogenesis and Mitophagy: Mtorc1 In Cancermentioning
confidence: 99%